An exploratory study of entrepreneurial social networks in the digital age. Issue 1 (15th September 2021) - Zhao, Fang; Barratt-Pugh, Llandis; Standen, Peter; Redmond, Janice; Suseno, Yuliani
Abstract : Purpose: Drawing on social network and social capital literature, this study aims to explore how digital entrepreneurs utilize social networks to build their entrepreneurial capability, creating and developing business ventures in a digitally networked society. Design/methodology/approach: The study takes a qualitative approach, interviewing 35 digital entrepreneurs with businesses operating across multiple industry sectors in Western Australia. Findings: The findings suggest that structural social capital provides a key resource with groups of relational contacts who facilitate in building entrepreneur capability, the venture and customer markets. Relational social capital provides a foundation of trust between entrepreneurs and social network members that is strategically important for digital entrepreneurship (DE). Cognitive social capital provides mechanisms to form relationships based on shared values across social networks. Research limitations/implications: The study produces early evidence that in a multiplexed networking world, social capital accrual and use online is different from that of off-line. More empirical studies are needed to understand the complexity of the changing nature of online and off-line social networks, the consequential social capital and their interdependence in DE. Practical implications: This is an exploratory qualitative study using a limited sample of 35 Australian digital entrepreneurs to explore the impact of social network interaction on digital entrepreneurs and their ventures, with the purpose of stimulating a social network approach when studying DE. This study confirms the critical importance of entrepreneurial social networks in the digital age and provides empirical evidence that online networks foster business development, while off-line networks feed self-development. Originality/value: The study contributes to current research on DE as a dedicated new research stream of entrepreneurship. Specifically, the study contributes to a greater understanding of how digital entrepreneurs leverage social networks in today's digitally connected society.